TEACHER FEEDBACK AND STUDENT RESPONSES IN A GRADE 9 INDONESIAN EFL CLASSROOM: AN IRF-BASED DISCOURSE ANALYSIS - Anggun Siska Pratiwi (INSPIRATION: Instructional Practices in Language Education, 2026)
Classroom interaction and teacher feedback play a crucial role in shaping students’ participation in English as a Foreign Language (EFL) learning. Classroom discourse is commonly organized through the Initiation–Response–Feedback (IRF) pattern, in which the teacher’s feedback move may either terminate or extend interactional opportunities. This study aimed to investigate IRF patterns and examine how teacher feedback was constructed and utilized to manage student participation in a Grade 9 Indonesian EFL classroom. A descriptive qualitative design was employed using a Classroom Discourse Analysis approach. Data were collected through classroom observation, audio recording of an 80-minute lesson, and transcription of teacher–student interaction. The data were analyzed using Sinclair and Coulthard’s IRF model combined with an interactive qualitative analysis framework. The findings indicate that classroom interaction was predominantly teacher-initiated, with evaluative feedback occurring most frequently. However, probing and reformulative feedback were found to encourage longer student responses and sustain participation. The study concludes that the pedagogical function of feedback within IRF sequences is crucial in shaping interactional dynamics and promoting student engagement in EFL classrooms. These findings highlight the importance of using feedback strategically not only as an evaluative tool but also as an interactional resource that supports extended classroom discourse and learner participation.